1999
DOI: 10.1088/0953-2048/12/12/330
|View full text |Cite
|
Sign up to set email alerts
|

Processing and superconducting properties of Hg1-xRexBa2Ca2Cu3O8+delta

Abstract: In this work we discuss one of the principal parameters to control for producing pieces of (Hg,Re)-1223 for device applications. The first prerequisite is the mixing of the cations which should be as good as possible and the degree of oxygen in the phase. The influence of the precursor oxygenation is discussed. It is shown that overdoped samples of (Hg,Re)-1223 have an increased irreversibility line. Finally the possibility of reprocessing sintered superconducting samples is shown, a very important aspect for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This could mean that the overdoping is obtained under the thermal treatment conditions applied in the synthesis process. In a previous work it was demonstrated that the "nal oxygen content of the (Hg,Re)-1223 as-prepared superconducting samples (39,46) can be de"ned during the precursor synthesis.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…This could mean that the overdoping is obtained under the thermal treatment conditions applied in the synthesis process. In a previous work it was demonstrated that the "nal oxygen content of the (Hg,Re)-1223 as-prepared superconducting samples (39,46) can be de"ned during the precursor synthesis.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…The mercury pressure is much larger than the oxygen partial pressure and the knowledge of the total pressure might be sufficient in a first approximation. Sin et al [22,23], developed some simple equipment to measure this pressure in situ: the so-called thermobaric analyser (TBA) and this is an adaptation of a Bourdon manometers see figure 5. The total pressure is probed by the displacement of a quartz spiral amplified by a quartz rod.…”
Section: Mercuration In Close Quartz Ampoule: In Situ Measurement Of ...mentioning
confidence: 99%